Method for monitoring thickness of Poly layer in preparation process of TOPCon battery
Monitoring the thickness of the Poly layer in the TOPCon battery by observing the size of the side tower base with a light microscope solves the problem of difficulty in effectively monitoring the thickness of the Poly layer in the existing technology, achieves precise monitoring and improves efficiency, and reduces production costs.
Patent Information
- Application Number
- CN202411451439.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively monitor and control the thickness of the Poly layer in TOPCon batteries, resulting in increased efficiency losses and production costs.
During the thinning process of the Poly layer in the non-grid line area, use a light microscope to observe the size of the side tower base and compare it with the standard value to monitor the thickness of the Poly layer. This method does not require expensive SEM equipment or model fitting, is simple and easy to implement, and is suitable for daily monitoring of production lines.
It achieves precise monitoring of the Poly layer thickness, reduces production costs, improves detection efficiency, and helps TOPCon batteries improve efficiency and move towards the efficiency target of 27%+.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of TOPCon battery processing, and in particular relates to a method for monitoring the thickness of a Poly layer during the preparation process of a TOPCon battery. Background Art
[0002] The theoretical efficiency of TOPCON cells is 28.7%, and the current mass production efficiency is generally 25.5-26.3%. Analyzing the actual cell efficiency loss has a strong guiding significance for improving the efficiency of TOPCon cells in the future. The efficiency loss of the cell is mainly divided into three parts: optical loss, electrical loss, and composite loss. Optical loss is mainly caused by the shading of the front grid line and the reflection of light. It can be reduced by reducing the area of the front surface grid line, making the front surface velvet to increase the optical path and form a light trapping structure; electrical loss is mainly caused by poor silver silicon contact and weak carrier lateral transmission ability. This part of the loss can be reduced by optimizing the silver silicon contact and improving the quality of the Poly layer. Composite loss is divided into gold semi-contact loss and parasitic absorption loss. The gold semi-contact loss can be replaced by a passivation contact on the front surface of the current TOPCon cell. The preparation of the Poly layer on both the front and back surfaces will bring additional parasitic absorption. How to reduce parasitic absorption has become the key to TOPCON cells moving towards 27%+ efficiency.
[0003] Polyfinger structure batteries are considered to be the mass-produced form of the next generation of TOPCon. They use a special process to remove the Poly layer in the non-grid area to reduce parasitic absorption, thereby achieving the purpose of improving battery efficiency. The main reasons that currently limit the implementation of Polyfinger structure batteries are: 1. The Poly layer in the grid area must be kept from being corroded; 2. The Poly thinning window in the non-grid area is small. If the thinning amount is too small, the efficiency advantage cannot be reflected. If the thinning amount is too large, it will affect the passivation effect of the Poly layer, so the thinning amount needs to be precisely controlled.
[0004] There are two main technical solutions for measuring the thinned Poly layer:
[0005] Method 1: Ellipsometer is based on measuring the change in polarization state of linear polarized light after it is reflected by a thin film sample. The thickness of the film, interface and surface roughness layer, as well as the optical properties, etc. are obtained through model fitting. The measurable thickness range is from a few angstroms to tens of nanometers. However, the ellipsometry (ellipsometer for short) uses software fitting to calculate the thickness of the Poly film. Its accuracy is heavily dependent on the reliability of the established model. The film thickness is obtained according to the ellipsometric equation. The direct conversion of Ψ and Δ is only possible under very ideal conditions, that is, isotropic and homogeneous particularly thick film conditions. In actual production, different annealing conditions lead to different film crystallinity and substrate roughness, which will lead to data deviations measured by the model.
[0006] Method 2: Scanning electron microscope uses a finely focused electron beam to perform raster scanning on the sample surface, and observes and analyzes the composition, morphology and structure of the sample surface by detecting signals such as secondary electrons, backscattered electrons and characteristic X-rays generated by the interaction between electrons and samples. However, scanning electron microscope (SEM) uses electron imaging to directly measure and does not have the problem of fitting deviation. However, SEM equipment is expensive and complicated to operate, so it is not suitable for daily monitoring of production lines. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for monitoring the thickness of the Poly layer during the preparation process of TOPCon batteries. This method does not require expensive SEM equipment or modeling and fitting. It only needs to be observed through a light microscope and compared with the prepared standard value to complete the monitoring, which is convenient for IPQC personnel to monitor.
[0008] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:
[0009] A method for monitoring the thickness of a Poly layer during the preparation of a TOPCon battery, the method comprising:
[0010] S1. During the thinning process of the Poly layer in the non-grid area, the size of the side tower base is observed using an optical microscope;
[0011] S2. Compare the side tower base size observed by the optical microscope with the standard value to monitor the thickness of the Poly layer.
[0012] In some embodiments, the process of observing the size of the side tower base using an optical microscope in step S1 is: taking a piece at the RCA unloading point, observing it using an optical microscope, and obtaining the size of the side tower base in conjunction with a scale.
[0013] In some embodiments, during the thinning process of the Poly layer in the non-gate line area in step S1, the back Poly layer and the side tower base both react with the alkaline solution.
[0014] In some embodiments, the alkali solution is a potassium hydroxide solution or a sodium hydroxide solution.
[0015] In some embodiments, the alkali solution is sodium hydroxide solution.
[0016] In some embodiments, the calculation formula of the standard value is D=k1(Aa) / k2, where D is the thinning thickness of the Poly layer, A, that is, the standard value, is the size of the side tower base observed under a light microscope, a is the size of the tower base after de-coating, k1 is the corrosion rate of the Poly layer in the alkaline solution, and k2 is the growth rate of the side tower base in the alkaline solution.
[0017] In some embodiments, the calculation formula is used to calculate the standard value A according to the set D, and k1 is 0.89 and k2 is 0.1068.
[0018] In some embodiments, during the thinning process of the Poly layer in the non-gate line area in step S1, the temperature is controlled at 65-75°C.
[0019] In some embodiments, in step S2, the observed side tower base size observed under a light microscope is compared with the standard value. When the standard value -3μm≤the side tower base size observed under a light microscope≤the standard value+3μm, it is in compliance with the standard requirements; when the side tower base size observed under a light microscope≤the standard value+6μm and does not meet the standard requirements, it is a concession to accept the requirements; otherwise, it does not meet the requirements and needs to be reworked.
[0020] In some embodiments, the thinned thickness of the Poly layer is ≤0.13 μm.
[0021] Beneficial effects:
[0022] The present invention provides a simple method for judging the remaining thickness after the Poly layer is thinned. The thinning of the back Poly layer needs to react in an alkali solution. At this time, the tower base on the side of the battery will also react with the alkali: 2NaOH+Si+H2O=Na2SiO3+2H2. The side tower base will continue to grow with the reaction with the alkali. Therefore, the thickness of the thinned back Poly layer can be judged by observing the size of the side tower base through an optical microscope. The method does not require SEM equipment and ellipsometers, only ordinary optical microscopes are needed for monitoring, and monitoring can be completed based on comparison with standard values. The monitoring personnel only need to learn how to operate an optical microscope to take up their posts, which reduces costs and improves detection efficiency compared to using SEM and ellipsometers. DETAILED DESCRIPTION
[0023] The following will be described clearly and completely in conjunction with the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0024] The components of the embodiments of the present invention generally described and shown herein may be arranged and designed in a variety of different configurations. Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention.
[0025] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0026] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0027] The present invention is applicable to various methods for preparing back TOPCon cells, but the most applicable method is the mask method.
[0028] The specific process of the mask method is:
[0029] The specific process of preparing back TOPCon cells by mask method is as follows:
[0030] (1) Take a 0.5-1.1Ω·cm battery cell;
[0031] (2) cleaning and velveting, using alkali to wash away the surface damage layer and prepare a pyramid velvet structure;
[0032] (3) Boron diffusion, using BCl3 as a boron source to dope the front surface of the silicon wafer to form a P layer;
[0033] (4) De-winding and alkali polishing to remove BSG on the side and back of the silicon wafer, and polishing the back with alkali to form a tower base with a diameter of 6 to 10 μm on the back and 7 to 11 μm on the side of the silicon wafer;
[0034] (5) LPCVD, using low-pressure vapor deposition to grow a tunnel oxide layer and a Poly layer on the back side;
[0035] (6) Phosphorus diffusion: phosphorus doping of the Poly layer;
[0036] (7) Remove the front plating and the back PSG; after removing the front and side Poly plating, the side tower base is 19-20μm;
[0037] (8) a back-side gate printing mask, the main component of which is silicon dioxide;
[0038] (9) Cleaning and etching to thin the non-gate line area and remove the front and back oxide layers;
[0039] (10) ALD, using atomic deposition method to deposit aluminum oxide on the front side;
[0040] (11) a front anti-reflection layer, which is formed by depositing three layers of silicon nitride, one layer of silicon oxynitride and one layer of silicon oxide in sequence;
[0041] (12) a back anti-reflection layer, which is composed of three silicon nitride layers with different refractive indices deposited in sequence;
[0042] (13)Metalization.
[0043] The monitoring process of the present invention is in step (9).
[0044] The specific monitoring methods are:
[0045] The standard value is calculated using the standard value calculation formula D=k1(Aa) / k2, where D is the thinning thickness of the Poly layer, A, i.e. the standard value, is the size of the side tower base observed under a light microscope, a is the size of the tower base after de-winding, k1 is the corrosion rate of the Poly layer in an alkaline solution, and k2 is the growth rate of the side tower base in an alkaline solution. According to the set D, the standard value A is calculated, and k1 is 0.89, k2 is 0.1068, and a is the size of the tower base after de-winding, which can be measured. At the same time, the value of a is the average value of the tower base size after de-winding of N pieces of standard back TOPCon batteries, N>20.
[0046] This standard value is found in a large number of experiments and actual production processes. When the Poly layer reacts in alkali solution, the reaction speed can be controlled by controlling the concentration and temperature of the alkali solution. The applicant surprisingly found that the etching of the Poly layer within the range of 130nm is linear with time, that is, the thickness of the Poly layer is D=k1t, k1 is the corrosion rate of the Poly layer in the alkali solution, and t is the reaction time. The growth of the side tower base is much more complicated than the Poly etching, but it can still show a linear growth with time within the thinning range of the Poly layer, that is, the size of the side tower base A=k2t+a, k2 is the growth rate of the side tower base in the alkali solution, t is the reaction time, and a is the size of the tower base after de-coating. Therefore, when the reaction occurs in the same solution, the reaction time is the same, and the relationship between the thinning thickness and the size A of the side tower base observed under a microscope can be obtained: D=k1(Aa) / k2. The conclusions found and summarized can be well applied in the actual production process, increasing the monitoring efficiency and reducing the monitoring cost.
[0047] A method for monitoring the thickness of a Poly layer during the preparation of a TOPCon battery, the method comprising:
[0048] S1. During the thinning process of the Poly layer in the non-grid area, the temperature is controlled at 65-75°C, and a sheet is taken from the RCA feeder, and the side tower base size is obtained by observation with a light microscope and a scale ruler;
[0049] S2. Compare the side tower base size observed by the optical microscope with the standard value to monitor the thickness of the Poly layer.
[0050] The thinning thickness of the Poly layer is ≤0.13μm.
[0051] During the thinning process of the Poly layer in the non-gate line area in step S1, the back Poly layer and the side tower base react with an alkali solution; the alkali solution is a potassium hydroxide solution or a sodium hydroxide solution, and the best alkali solution is a sodium hydroxide solution.
[0052] Judging criteria: Compare the size of the side tower base observed under a light microscope with the standard value. When the standard value -3μm ≤ the size of the side tower base observed under a light microscope ≤ the standard value +3μm, it is in compliance with the standard requirements; when the size of the side tower base observed under a light microscope ≤ the standard value +6μm and does not meet the standard requirements, it is a concession to accept the requirements; otherwise, it does not meet the requirements and needs to be reworked.
[0053] For step 5, deposit a 130nm thick Poly layer, set the thinning range to 40-50nm, measure the size of the tower base after de-plating, and calculate: the side tower base range / μm that meets the standards is 22.9-24.1, the side tower base range / μm that is accepted with concessions is 24.1-30.1or<22.9, and the side tower base range / μm that is reworked is>30.1.
[0054] The above preparation forms a standard table, which is used to monitor the production process. The standard table is as follows:
[0055]
[0056] It can be seen from the standard table that there are three judgment criteria: the first level, the side tower base is 22.9~24.1μm, indicating that the remaining Poly layer thickness is qualified, allowing the silicon wafer to continue to be transferred to the next process; the second level, the side tower base is between 24.1~30.1μm or <22.9μm, indicating that the remaining Poly layer thickness is on the qualified boundary line, and the silicon wafer is allowed to continue to be transferred to the next process; the third level, the side tower base range is >30.1μm, indicating that the remaining Poly layer thickness is unqualified and the silicon wafer needs to be reworked.
[0057] After cleaning and etching, as the side tower base grows, the remaining Poly on the back side gradually decreases. When the side tower base is 30.1μm, if it continues to increase, the side tower base will be too large and may even be washed through to the tunnel oxide layer. This will bring two adverse consequences. First, the too-thin Poly layer cannot play the role of back passivation, resulting in a decrease in Voc; second, the too-thin Poly layer cannot provide the effect of collecting lateral current, resulting in a decrease in I sc. When the side tower base is 22.9μm, it means that the thinning of the back Poly layer is not enough, and the expected benefit of this process is not obvious, so it can be accepted as a compromise.
[0058] The standard table can be placed at the material unloading place after the process in step 9 is completed, and a piece can be taken every 2 hours to observe and record using a light microscope. Make a selection based on different results.
[0059] Example 1
[0060] The TOPCON battery process route of the Poly finger structure based on the printing mask method is to carry out cleaning and texturing, boron diffusion, oxidation, alkaline polishing, LP, phosphorus diffusion, de-plating, printing mask, cleaning and etching, front and back film, and metallization in sequence. After the cleaning and etching process, the silicon wafers are collected and the tower base size is tested. The silicon wafers with the side tower base of 23.5±0.1μm are taken and compared with the standard table. After marking, they flow to the back-end to check the efficiency.
[0061] Example 2
[0062] The TOPCON battery process route of the Poly finger structure based on the printing mask method is to carry out cleaning and texturing, boron diffusion, oxidation, alkaline polishing, LP, phosphorus diffusion, de-plating, printing mask, cleaning and etching, front and back film, and metallization in sequence. After the cleaning and etching process, the silicon wafers are collected and the tower base size is observed and tested through an optical microscope. The silicon wafers with side tower bases of 25.3±0.1μm are taken and compared with the standard table. After marking, they flow to the back-end to check the efficiency.
[0063] Comparative Case 1
[0064] The TOPCON cell process route of the Poly fi nger structure based on the printing mask method is to carry out cleaning and texturing, boron diffusion, oxidation, alkaline polishing, LP, phosphorus diffusion, de-wrap plating, printing mask, cleaning and etching, front and back film, and metallization in sequence. After the cleaning and etching process, the silicon wafers are collected and the tower base size is tested. The silicon wafers with the side tower base of 23.5±0.1μm are taken, fitted by the ellipsometer, marked, and flowed to the back-end to check the efficiency.
[0065] Comparative Example 2
[0066] The TOPCON cell process route of the Poly fi nger structure based on the printing mask method is to carry out cleaning and texturing, boron diffusion, oxidation, alkaline polishing, LP, phosphorus diffusion, de-plating, printing mask, cleaning and etching, front and back film, and metallization in sequence. After the cleaning and etching process, the silicon wafers are collected and the tower base size is tested. The silicon wafers with the side tower base of 25.3±0.1μm are taken, fitted by the ellipsometer, marked, and flowed to the back-end to check the efficiency.
[0067] The TOPCON batteries produced in Example 1, Example 2 and Comparative Example 1 and Comparative Example 2 were tested according to the Rhine standard. The test results are as follows:
[0068]
[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for monitoring the thickness of a Poly layer during the preparation of a TOPCon battery, characterized in that: The method includes: S1. During the thinning process of the Poly layer in the non-grid area, use an optical microscope to observe the size of the side tower base; S2. Compare the side tower base size observed by the optical microscope with the standard value to monitor the thickness of the Poly layer.
2. The method for monitoring the thickness of the Poly layer during the preparation of the TOPCon battery according to claim 1, characterized in that: The process of observing the size of the side tower base using an optical microscope in step S1 is as follows: taking a piece at the RCA unloading location, observing it using an optical microscope, and obtaining the size of the side tower base in conjunction with a scale.
3. The method for monitoring the thickness of the Poly layer during the preparation of the TOPCon battery according to claim 2, characterized in that: During the thinning process of the Poly layer in the non-gate line area in step S1, the back Poly layer and the side tower base react with the alkali solution.
4. The method for monitoring the thickness of the Poly layer during the preparation of the TOPCon battery according to claim 3, characterized in that: The alkali solution is potassium hydroxide solution or sodium hydroxide solution.
5. The method for monitoring the thickness of the Poly layer during the preparation of the TOPCon battery according to claim 3, characterized in that: The alkali solution is sodium hydroxide solution.
6. The method for monitoring the thickness of the Poly layer during the preparation of the TOPCon battery according to claim 1, characterized in that: The calculation formula of the standard value is D=k1(Aa) / k2, wherein D is the thinning thickness of the Poly layer, A, i.e. the standard value, is the size of the side tower base observed under a light microscope, a is the size of the tower base after de-coating, k1 is the corrosion rate of the Poly layer in alkaline solution, and k2 is the growth rate of the side tower base in alkaline solution.
7. The method for monitoring the thickness of the Poly layer during the preparation of the TOPCon battery according to claim 5, characterized in that: The calculation formula is used to calculate the standard value A according to the set D, and the k1 is 0.89 and k2 is 0.1068.
8. The method for monitoring the thickness of the Poly layer during the preparation of the TOPCon battery according to claim 1, characterized in that: In the step S1, during the thinning process of the Poly layer in the non-gate line area, the temperature is controlled at 65-75°C.
9. The method for monitoring the thickness of the Poly layer during the preparation of a TOPCon battery according to claim 1, characterized in that: In step S2, the observed side tower base size observed under the optical microscope is compared with the standard value. When the standard value -3μm≤the side tower base size observed under the optical microscope≤the standard value+3μm, it is in compliance with the standard requirements; when the side tower base size observed under the optical microscope≤the standard value+6μm and does not meet the standard requirements, it is a concession to accept the requirements; otherwise, it is not in compliance with the requirements and needs to be reworked.
10. The method for monitoring the thickness of the Poly layer during the preparation of a TOPCon battery according to claim 1, characterized in that: The thinned thickness of the Poly layer is ≤0.13 μm.